ANALISIS PERBANDINGAN KINERJA LEMBAGA KEUANGAN BANK DAN NON BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Friska Ko’ke, Vinsensya (JURNAL BISNIS KOLEGA, 2023)
The comparative analysis of the performance of bank and non bank financial institutions listed on the Indonesia stock exchange. From the result of the reseacsh and discussion conducted. the outors conclude that a comporative analysis of the performance of bank and non-bank financial over the last three years. Namely, ban financial institution and non-bank analyzed using the ratios of CR,ROA,ROE,DAR,and DER. Based on predetermined sample criteria, two research sample groups were selected, namely two financial instutions. The statical analysis tool used to prove the hypothesis in this study is the independent sample T-test